Fabry disease and enzyme replacement therapy in classic patients with same mutation: different formulations – different outcome?. Issue 1 (20th April 2015) - Politei, J.; Schenone, A.B.; Cabrera, G.; Heguilen, R.; Szlago, M.
Abstract : We describe the results of the multidisciplinary evaluation in patients with Fabry disease and the same genetic mutation and their outcomes using different approved enzyme replacement therapy (ERT). We measured baseline data and serial results of neuropathic pain assessment and renal, cardiac and cerebrovascular functioning. Pain scale showed improvement in all male cases treated with agalsidasa beta. A mild improvement was detected in agalsidasa alfa‐treated patients after 1 year with posterior increase. During the agalsidase beta shortage, two male patients were switched to agalsidasa alfa, after 1 year both cases presented an increase in scale values. Renal evolution showed a tendency toward a decrease in proteinuria in patients using agalsidase beta and worsening with agalsidase alfa. We found improvement in two females using agalsidase beta and no changes in the other cases regarding cardiac functioning. Brain magnetic resonance imaging (MRI) showed increase of white matter lesions in four patients. Improvement and stabilization in neuropathic pain, renal and cardiac functioning and brain MRI were found mainly in patients treated with agalsidase beta. Following the reported recommendations on reintroduction of agalsidase beta after the enzyme shortage, we decided to switch all patients to agalsidase beta.